STEPS IN THE PROCESS OF IDENTIFYING FULL-TEXT SIMILARITIES IN A MULTILINGUAL DATABASE - Bekchanov Hikmat Mansurbek o’g’li; Babayev Saidmukhammadjon Saidkamolovich; Shermatov Boburjon Inoyat O‘g‘li; Avezmatov Ikhtiyor Davlatyarovich (Ustozlar uchun, 2025)
The article describes the processes of identifying similar texts from a multilingual full-text database: changing the text format, morphological analysis of words in the text, and storing them in the database.